Can Stria Gravidarum Predict Surgical Fluid Loss in Cesarean Section? - Seyma Banu Arslanca; Ozgur Sahin; Ugurkan Erkayıran; Zehra Ozturk Basarır; Tufan Arslanca (Mattioli1885, 2023)
Introduction: Alterations in collagen subtypes and matrix can potentially cause fluid loss in surgery which are important in terms of liqud loss. Objectives: The study aimed to analyze stria gravidarum (SG) and its severity in pregnant who had undergone cesarean section (CS) and to evaluate surgical fluid loss (SFL) that occurred during CS operation. Methods: The research was designed as a prospective clinical cohort study to compare the amount of SFL in the second cesarean section with the severity of SG at 34-37 weeks pregnant (n:308). The severity of SG was evaluated in the preoperative period using the Davey scoring. All patients were defined none, mild stria and severe stria. The SFL was calculated by weighing the pre-and post-operative weights of the sponges. Results: The weight gain (p=0,008) and BMI (p=0,017) gradually increased toward severe SG. In correlation analysis of SFL, a positive correlation was found with Davey (r=0.791; p=0.0001), weight gained during pregnancy (r=0.328;p=0.0001), BMI (r=0.453;p=0.001) and newborn's weight (r=0.139;p=0.003). In the ROC for the predictability of SG severity on SFL, severe SG showed a potential for SFL with %95.1 specificity and %93.2 sensitivity at 791 cut-offs (Area Under the Curve:0,987; p=0.00001; %95 Confidence Interval: 0.977-0.997). Conclusion: The SG severity and SFL showed a very strong relationship, which was a very important finding that would affect the approach of the surgeons to the patients with SG in terms of fluid loss in CS.